Updating concepts on atherosclerotic inflammation: From pathophysiology to treatment - Ministrini, Stefano; Carbone, Federico; Montecucco, Fabrizio (European journal of clinical investigation, 2021)
Background Atherosclerosis is recognized as a systemic low‐grade inflammatory disease. Furthermore, the dysregulation of the inflammatory response and its timely resolution is a pivotal process in determining the clinical manifestations of cardiac and cerebral acute ischaemia following atherothrombosis. Methods This narrative review is based on the material searched on PubMed up to October 2020. The search terms we used were as follows: "atherosclerosis, inflammation, acute myocardial infarction and ischemic stroke" in combination with "biomarker, inflammatory cells and molecules, treatment." Results The expected goal of addressing inflammation for the treatment of atherosclerosis and its acute ischaemic complications is reducing mortality and morbidity related to atherosclerotic cardiovascular disease, which are currently the first cause of death and disability worldwide. In this narrative review, we summarize the evidence about the main cellular and molecular mechanisms of inflammation in atherogenesis, atherothrombosis and acute ischaemic complications, with particular focus on the potential molecular targets for novel pharmacological treatments. Conclusion Although a large amount of evidence from animal models of atherothrombotic disease, and promising results of clinical trials, anti‐inflammatory treatments against atherosclerosis are not yet recommended. A deepest understanding of pathophysiological mechanisms underlying the mechanisms driving resolution of the acute inflammation will probably allow to identify the optimal molecular target.